Penentuan Cost of Good Sold dan Penerapan Cost Plus Pricing Method dalam Menentukan Harga Jual: Study Penggilingan Padi UD Budi Luhur - Erawati Kartika; M. Rifky Bakhtiar (Universitas Muhammadiyah Semarang, 2020)
The cost plus pricing approach in determining the cost of production is very important because this method is more detailed in including the cost components needed in a production process. This situation can affect the determination of the selling price and the resulting profits. The full costing model as the determination of the cost of goods manufactured (HPP) is expected to be a tool for UD Budi Luhur. This study aims to analyze how to determine the selling price at UD Budi Luhur with the selling price according to the cost plus pricing method. The method used is quantitative descriptive method. The results show that the management has not applied cost plus pricing analysis in calculating the selling price. The selling price generated by this method is lower than the method the company has used previously. UD Budi Luhur's management should begin to apply the cost plus pricing method by using a variable cost approach in calculating the selling price so that the selling price achieved by the company can compete with similar products on the market.